Patients’ experiences of a behavioural intervention for migraine headache: a qualitative study - Morgan, Myfanwy (J Headache Pain, 2016)
BACKGROUND: Migraine headache has a high prevalence and a severe impact on personal, social and work life, forming a significant burden on patients, service providers and society. There is some evidence of the effectiveness of behavioural interventions to supplement drug therapy but a recognised need to identify an effective minimal contact approach to enhance access and provide a model for use in publicly funded health systems. This study uses in-depth interviews to examine patients’ experience and responses to a behavioural intervention with relaxation and CBT components delivered in three individual therapist sessions with follow-up. METHODS: Qualitative study of 20 adults aged 18–75 years in London, UK, with clinically diagnosed migraine and at least four headache days per month. Semi-structured and tape recorded interviews were held post intervention based on a topic guide. Transcripts were coded and charted for all participants and analysed thematically. RESULTS: The majority of participants cited the impacts of migraine and a desire for additional non-drug treatment as their main reasons for taking part and almost all completed the course. They valued contact with the therapist and almost all reported benefiting from the therapy. Post intervention they used those techniques they found most beneficial and implemented them flexibly in their daily life to reduce stress and risks of migraine or to respond to migraine. Relaxation training (deep breathing) was easily adopted and often used post intervention. The CBT components were mainly viewed positively but regarded as more challenging to learn and implement. CONCLUSIONS: Patients’ selectively identified and employed the techniques learned as ‘tools’ to assist in preventing and managing their migraines, with reported benefits supporting the development of minimal contact behavioural therapy to increase accessibility for adults with migraine headache and the conduct of a definitive trial.